The ankle brachial index is associated with prognosis in patients with diabetic kidney disease. Issue 2 (May 2015) - Chang, Li-Hsin; Chu, Chia-Huei; Lin, Hong-Da; Kwok, Ching-Fai; Won, Justin G.S.; Chen, Harn-Shen; Lin, Liang-Yu
Highlights ABI is a CV risk factor. ABI or albuminuria associates wih diabetic outcomes. ABI < 0.9 plus albuminuria associats with the worst outcome.